Impact of flattening-filter-free radiation on the clonogenic survival of astrocytic cell lines = Einfluss von Flattening-Filter-freier Bestrahlung auf das klonogene Überleben von Astrozytomzelllinien - Steenken, Caroline; Fleckenstein, Jens; Jahnke, Lennart; Simeonova-Chergou, Anna; Hartmann, Linda; Kübler, Jens; Veldwijk, Marlon Romano; Wenz, Frederik; Herskind, Carsten; Giordano, Frank Anton (Strahlentherapie und Onkologie, 2015)
Background and purpose: Flattening-filter-free (FFF) beams are increasingly used in radiotherapy as delivery times can be substantially reduced. However, the relative biologic effectiveness (RBE) of FFF may be increased relative to conventional flattened (FLAT) beams due to differences in energy spectra. Therefore, we investigated the effects of FFF and FLAT beams on the clonogenic survival of astrocytoma cells. Material and methods: Three cell lines (U251, U251-MGMT, and U87) were irradiated with 6-MV and 10-MV X-rays from a linear accelerator in FFF- or FLAT-beam modes at dose rates in the range of 0.5-24 Gy/min. The surviving fraction (SF) as function of dose (2-12 Gy) was determined by the colony formation assay and fitted by the linear-quadratic model. For both beams (FFF or FLAT), the cells were pelleted in conical 15-ml centrifuge tubes and irradiated at 2-cm depth in a 1 × 1-cm2 area on the central axis of a 30 × 30-cm2 field. Dosimetry was performed with a 0.3-cm3 rigid ionization chamber. RBE was determined for FFF versus FLAT irradiation. Results: The RBE of FFF at 7.3-11.3 Gy was 1.027 ± 0.013 and 1.063 ± 0.018 relative to FLAT beams for 6- and 10-MV beams, respectively, and was only significantly higher than 1 for 10 MV. Significantly increased survival rates were seen for lower dose rates (0.5 Gy/min FLAT vs. 5 Gy/min FLAT) at higher doses (11.9 Gy), while no differences were seen at dose rates ≥ 1.4 Gy/min (1.4 Gy/min FFF vs. 14 Gy/min FFF and 2.4 Gy/min FFF vs. 24 Gy/min FFF). Conclusions: FFF beams showed only a slightly increased RBE relative to FLAT beams in this experimental set-up, which is unlikely to result in clinically relevant differences in outcome.
Gesehen am 15.03.2018